Advanced healthcare directives: an analysis of the ethical and legal related issues, and a current comparison among EU Members states - Vitale, Alessandro (Bioethica, 2019)
This paper deals with the never-enough-discussed topic of the end of life advanced decisions, focusing on the instructional advanced directives and other kinds of advance healthcare planning (like the appointment of a proxy), as forms of autonomy on own health and life – that is the right to self-determine in advance about whether to submit or not to some medical treatments, even the life-saving ones, in case of the future inability or unconsciousness at the moment they are required. This work aims to provide an overview of the current state of the art of the subject matter, starting from the reconstruction of the route that led to the achievement of such an important legal common framework as the informed consent principle (implemented at a European level by the Oviedo Convention of 1997), to get to the analysis of five EU Members States’ national regulations, comparing for the purpose the related similarities and differences, the strengths and the weaknesses; that is the Acts of Belgium, France, Germany, Spain, until the most recent at the moment, the Italian law on informed consent and advanced directives of the late 2017. The report highlights how there is not still a common view of the matter, particularly talking about the legal bindingness of the advanced directives; and even where it is provided, margins of inefficiency or ineffectiveness are more than a possibility, as many concrete cases continue to show, due to some gaps of the system. A lot of work still needs to be done at all levels, from the EU institutions to the national Parliaments, from the Courts to the hospitals wards, to enhance and grant the advanced will of the most weak among the patients, the unable ones to currently express their wishes; patients thatnevertheless, and even more so, deserve their personal liberty and their dignity to be respected.